Insights on Growth and Nanoscopic Investigation of Uncommon Iron Oxide Polymorphs. Issue 31 (19th September 2013) - Carraro, Giorgio; Maccato, Chiara; Bontempi, Elza; Gasparotto, Alberto; Lebedev, Oleg I.; Turner, Stuart; Depero, Laura E.; Van Tendeloo, Gustaaf; Barreca, Davide
Abstract: Si(100)‐supported Fe2 O3 nanomaterials were developed by a chemical vapor deposition (CVD) approach. The syntheses, which were performed at temperatures between 400 and 550 °C, selectively yielded the scarcely studied β‐ and ϵ‐Fe2 O3 polymorphs under O2 or O2 + H2 O reaction environments, respectively. Correspondingly, the observed morphology underwent a progressive evolution from interconnected nanopyramids to vertically aligned nanorods. The present study aims to provide novel insights into Fe2 O3 nano‐organization by a systematic investigation of the system structure/morphology and of their interrelations with growth conditions. In particular, for the first time, the β‐ and ϵ‐Fe2 O3 preparation process has been accompanied by a thorough multitechnique investigation, which, beyond X‐ray photoelectron spectroscopy (XPS) and field‐emission scanning electron microscopy (FESEM), is carried out by X‐ray diffraction (XRD), energy‐dispersive X‐ray spectroscopy (EDXS), atomic force microscopy (AFM), high‐resolution transmission electron microscopy (HRTEM), electron diffraction (ED), scanning TEM electron energy‐loss spectroscopy (STEM‐EELS), and high‐angle annular dark‐field STEM (HAADF‐STEM). Remarkably, the target materials showed a high structural and compositional homogeneity throughout the whole thickness of the nanodeposit. In particular, spatially resolved EELS chemical maps through the spectrum imaging (SI) technique enabled us to gain important information on the local Fe coordination, which is of crucial importance in determining the system reactivity. The described preparation method is in fact a powerful tool to simultaneously tailor phase composition and morphology of iron(III) oxide nanomaterials, the potential applications of which include photocatalysis, magnetic devices, gas sensors, and anodes for Li‐ion batteries. Abstract : We have developed an efficient vapor‐phase preparation method to selectively produce the scarcely investigated β‐ and ϵ‐Fe2 O3 nanostructured polymorphs. A detailed characterization highlights the crucial role of the growth temperature and reaction atmosphere (O2 versus O2 + H2 O) in tailoring the compositional, structural, and morphological properties of the system.